Role of hypothalamus function in metabolic diseases and its potential mechanisms - Zhang, Xinyu; Yang, Jie; Li, Yilin; Li, Yulin; Li, Guoqi (PeerJ, 2025)
The hypothalamus, a crucial neuroendocrine regulatory center, plays a significant role in the occurrence and development of metabolic diseases. Recent advances in molecular biology and imaging technology have facilitated a better understanding of the central role of the hypothalamus in the dysregulation of regulatory mechanisms. This review examines the involvement of hypothalamic nuclei in metabolic diseases, the direct effects of glucose and fat on the hypothalamus, and the influence of the hypothalamus on metabolic diseases. Furthermore, it investigates the role of the hypothalamus in the emergence and progression of metabolic disorders, including obesity and diabetes. Finally, it outlines the current research progress in treating metabolic diseases through hypothalamus regulation. This study could provide a theoretical basis for understanding the pathophysiological mechanisms of metabolic diseases and development of new treatment strategies.
Keywords: Hypothalamus; Obesity; Diabetes; Metabolic diseases; Hypothalamic nuclei